Las medidas para contrarrestar la crisis de la eurozona y su impacto en el modelo social europeo - Pinelli, Cesare (Revista de Derecho, 2019)
The Author seeks to demonstrate that the impact of the eurozone’s financial crisis onthe European social model is due both to scarce capacity of the EU political institutionsin managing that crisis and to the fact that, in the last decade, the launch of theEuropean social model was not accompanied with the political conditions aimed atmeeting the challenges posed from a powerful non-regulated global financial market.To this end, after having exposed the main features of the EU economic governance,the author draws attention on the instruments (Six pack, Fiscal Compact, ESM) recentlyadopted from the EU or its single member States with the aim of reacting to thefinancial crisis. According to the Author, the failures of these instruments depend onthe national governments’ anawareness of the risks posed from the current crisis forthe whole construction of the EU.
Keywords: European Social Model; Global Financial Crisis; Institutional Assessment